Consumers’ preference on goat’s milk based on sensory attributes - Ismail, Alia Khalidah; Mohd Nawi, Nolila; M. M., Ismail; Goh, Yong Meng (KAJ Printing, 2021)
Increasing global population has resulted in a corresponding increase in global demand for meat and milk. For high quality milk, the demand is particularly for goat’s milk due to consumers’ increasing awareness on its benefits. However, there remain negative perceptions associated with goat’s milk. Therefore, research on new feeding formulation (NFF) has to be undertaken to improve goat’s milk production and quality assurance. In the present work, a sensory evaluation was performed to analyse the characteristics of four different samples of fresh goat’s milk; two commercial, and two non-commercial. Face-to-face interviews using a structured questionnaire were conducted, utilising the Central Location Test (CLT) with 828 respondents being selected through the purposive sampling method. Data were analysed using descriptive analysis and one-way ANOVA. Based on the descriptive analysis outcomes, majority of the respondents (n = 662) had an experience consuming goat’s milk. They also perceived goat’s milk as fatty (n = 362) and sweet taste (n = 147). One-way ANOVA analysis on respondents’ perception indicated their desires for goat’s milk with attributes that are medium white, slightly weak of goaty aroma, and slightly viscous. They also favoured slightly sweet, slightly not salty, slightly creamy, and medium fresh milk. Next, the acceptance level of goat’s milk attributes of four different samples showed that sample B (researched sample) scored higher ranging between 5 (either like or dislike) to 7 (medium like), as compared to the other samples. Importantly, most respondents (59.7%; n = 494) chose sample B as the most preferred milk. Therefore, the findings of the present work provided a solid basis in understanding the sensory characteristics of goat’s milk most preferred by consumers to be used in product development and quality assurance by food processors and marketers.